Objective measurements analysis for usability evaluation of mobile applications for deaf people - Nathan, Shelena Soosay; Hussain, Azham; Hashim, Nor Laily (Universiti Teknikal Malaysia Melaka, 2017)
Usability evaluation is an important element that will enable to identify performance of any system or application.Through identification of these issue, usefulness of a product can be improvised.Many usability models are available to evaluate the system usability.Usability data can be collected in two different method which is objective data and subjective data.This paper present objective data analysis of usability evaluation conducted with deaf people mobile application.The results show that the application evaluated having usability issue in term of performance which needs to be improvised by the developer to produce better functionality application for deaf people.